Coupled and decoupled on-chip solenoid inductors with nanogranular magnetic cores. (December 2017) - He, Yuhan; Wang, Luo; Wang, Yicheng; Zhang, Huaiwu; Peng, Dongliang; Bai, Feiming
Abstract: On-chip integrated solenoid inductors with multilayered nanogranular magnetic cores have been designed and fabricated on silicon wafers. Both decoupled and coupled inductors with multilayered magnetic cores were studied. For the decoupled inductor, an inductance of 14.2 nH or an equivalent inductance area density greater than 100 nH/mm 2 was obtained, which is about 14 times of that of the air-core inductor, and the quality factor is 7.5 at 130 MHz. For the coupled inductor, an even higher peak quality factor of 17 was achieved at 300 MHz, however, the inductance area density decreased to 34 nH/mm 2 . The reason of the enhanced peak quality factor was attributed to less spike domains on the edge of the closure-loop shaped magnetic core, and therefore higher permeability and more uniform uniaxial anisotropy.